2018
DOI: 10.2478/acss-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis in Latvian and Russian: A Survey

Abstract: Social networking sites such as Facebook, Twitter and VKontakte, online stores such as eBay, Amazon and Alibaba as well as many other websites allow users to share their thoughts with their peers. Often those thoughts contain not only factual information, but also users’ opinion and feelings. This subjective information may be extracted using sentiment analysis methods, which are currently a topic of active research. Most studies are carried out on the basis of texts written in English, while other languages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Koltsova and Nagornyy examined which topics were defined as social problems by reviewing the comments of the audiences of the regional mass media in Russia [57]. They collected a dataset of 33,887 news items and 258,107 comments from local online media sources in Omsk (Gorod55 9 , BK55 10 , NGS Omsk 11 , and Omsk-Inform 12 ) during the period from September 2013 to September 2014. To extract topics from news texts, the authors applied the Gensim [117] implementation of the Latent Dirichlet Allocation algorithm [102] with a metric by Arun, Suresh, Madhavan and Murthy [118].…”
Section: C: Social Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koltsova and Nagornyy examined which topics were defined as social problems by reviewing the comments of the audiences of the regional mass media in Russia [57]. They collected a dataset of 33,887 news items and 258,107 comments from local online media sources in Omsk (Gorod55 9 , BK55 10 , NGS Omsk 11 , and Omsk-Inform 12 ) during the period from September 2013 to September 2014. To extract topics from news texts, the authors applied the Gensim [117] implementation of the Latent Dirichlet Allocation algorithm [102] with a metric by Arun, Suresh, Madhavan and Murthy [118].…”
Section: C: Social Tensionmentioning
confidence: 99%
“…Only one survey [10] by Viksna and Jekabsons directly addressed the sentiment analysis of Russian content, and several others [11]- [14] mentioned sentiment analysis of Russian in the contexts of overall comparison with globally existing approaches. There were other studies dedicated to specific aspects of sentiment analysis of Russian, for instance, the evaluation of state-of-the-art approaches [15]- [18], comparison of neural network architectures for sentiment analysis [19], [20], and comparison of publicly available Russian sentiment lexicons [21].…”
Section: Introductionmentioning
confidence: 99%
“…The corpus is available on Github 4 , in accordance with the content redistribution section of the Twitter Developer Agreement and Policy 5 . The public release includes tweet IDs along with data fields created within the scope of this project (starting with "location_lng" in Figure 1).…”
Section: The Twitter Eater Corpusmentioning
confidence: 99%
“…We compared a Python implementation of the Naive Bayes classifier from NLTK [14] against Pinnis [3] implementation of the Perceptron classifier. We also experimented with several combinations of training data sets -TE (our Twitter Eater dataset), MP [3], RV [5], PE [4], NI 11 . We found that the highest classification accuracy -61.23 % -is achieved by using all but NI data sets for training and only stemming all words.…”
Section: Questionmentioning
confidence: 99%
See 1 more Smart Citation